Blind Search of the Solar Neighborhood Galactic Disk within 5 kpc: 1179 New Star Clusters Found in Gaia DR3 - Huanbin Chi; Feng Wang; Wenting Wang; Hui Deng; Zhongmu Li (The Astrophysical Journal Supplement Series, 2023)
Studying open clusters (OCs) may help to provide a comprehensive understanding of the structure and evolution of the Milky Way. Many previous studies have systematically searched for OCs near the solar system within 1.2 kpc or 20° of Galactic latitude. However, few studies have searched for OCs at higher Galactic latitudes and deeper distances. In this study, based on a hybrid unsupervised clustering algorithm (friends-of-friends and pyUPMASK) and a binary classification algorithm (random forest), we extended the search region (i.e., Galactic latitude $\left|b\right|\geqslant 20^° )$ and performed a fine-grained blind search for Galactic clusters in Gaia DR3. After crossmatching, the newly discovered cluster candidates are fitted using isochrone fitting to estimate the main physical parameters (i.e., age and metallicity) of these clusters. These cluster candidates were then checked using manual visual inspection. Their statistical properties were also compared with previously exposed cluster catalogs. We found 1179 new clusters with considerable confidence within 5 kpc.